2017
DOI: 10.1007/s10534-017-0054-6
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium(V) complexes with hydrazides and their spectroscopic and biological properties

Abstract: The present study explores the synthesis and inhibitory potential of vanadium(V) complexes of hydrazides (1c-12c) against oxidative enzymes including xanthine oxidase and lipoxygenase (LOX). In addition, non-enzymatic radical scavenging activities of these complexes were also determined. On the basis of spectral, elemental and physical data, synthesized vanadium(V) complexes are tentatively assigned to have an octahedral geometry with two hydrazide ligands and two oxo groups forming a negatively charged sphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…All of the aroylhydrazine ligands ( Figure 1) have been synthesized and characterized previously. The physical and analytical data of these synthesized ligands have been described [7][8][9][10][11][12][13][14][15]. Aroylhydrazine ligands (1-7) were re synthesized here from previous method [13].…”
Section: Synthesis Of Aroylhydrazine Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…All of the aroylhydrazine ligands ( Figure 1) have been synthesized and characterized previously. The physical and analytical data of these synthesized ligands have been described [7][8][9][10][11][12][13][14][15]. Aroylhydrazine ligands (1-7) were re synthesized here from previous method [13].…”
Section: Synthesis Of Aroylhydrazine Ligandsmentioning
confidence: 99%
“…Synthesis and structural studies of aroylhydrazine ligands (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) have reported previously [7][8][9][10][11][12][13][14][15]. Chromium(III)-aroylhydrazine complexes (8a-12a) were discussed in reference [13] while remaining chromium(III) complexes (1a-7a) with aroylhydrazine ligands (1-7) are specified in Figure 1 and Scheme 1.…”
Section: Synthesis and Physicochemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation